HUBUNGAN ANTARA FLUKTUASI NILAI TUKAR RUPIAH, SUKU BUNGA DAN HARGA SAHAM INDUSTRI MANUFAKTUR DI BURSA EFEK JAKARTA - Budiantara, M. (KINERJA, 2003)
In this study, we examine the relation between exchange rate, interest rate, and stock price of manufacturing industries. Despite Engle-Granger procedure and Johansen Criterion, error correction model (ECM) of the two variables is employed to simultaneously estimate the short run and long run dynamics of the variables. Using monthly data covering the May 1996 – September 2003 period, empirical results show that there is a causal relation between variables in the crisis period and before the crisis period. The result of the ECM estimation proves that an increase in stock price of manufacturing industries has a positive effect on the exchange rate, because foreign investors enter the domestic stock market. Depreciation of domestic currency has a negative effect on the stock price. In the crisis period, we can prove that the stock price has a significant effect on the exchange rate variable in the long run. We also prove that the effect of the exchange rate on the stock price only occur in the long run. On the other hand, the result of ECM estimation also proves that an increase in deposit rate has a negative effect on the stock price in the long run and in the short run, because the gain from the deposit would be more than the gain from stock exchange, and we also prove that the stock price of manufacturing industries has a significant effect on the deposit rate variable only in the short run.Keywords: exchange rate, stock price, interest rate, Error Correction Model